Pulleniatina Minimum Events in the Andaman Sea (NE Indian Ocean): Implications for winter monsoon and thermocline changes - Sijinkumar, A. V.; Nath, B. Nagender; Possnert, G.; Aldahan, A. (Marine Micropaleontology, 2011)
The late Quaternary record of Pulleniatina obliquiloculata was investigated from two well dated sediment cores from the Andaman Sea (NE Indian Ocean) to examine its paleoceanographic significance and the presence of the Pulleniatina Minimum Events (PME) in the western North Pacific. As in the Pacific, our study shows that PMEs exist in the Indian Ocean albeit with a lower intensity. The Holocene PME occurs between 4.5 and 3.0 cal ka BP with a considerable reduction in P. obliquiloculata abundance, and which matches well with the Pacific records influenced by the Kuroshio Current. Additionally, two significant minimum events of P. obliquiloculata are also seen during the Younger Dryas (YD) and late Last Glacial Maximum (LGM, 20–18 cal ka BP). Overall, the PMEs of the Andaman Sea are not current driven events like in the western Pacific margin either by the weakening of the Kuroshio Current or reduced winter SSTs. The PMEs of the Andaman Sea are characterised by lower abundances of thermocline species indicating the increased depth of the thermocline (DOT) and reduced winter SSTs mainly during the minimum events of the YD and late LGM. The high SSTs during the Holocene PME make this event a mystery. However, the presence of PMEs in the Andaman Sea suggests that these events are not confined to areas influenced by the Kuroshio Current but may be responding to a broad scale oceanographic–climatic process or mechanism which needs to be explored with a detailed study.
id: 2159